Odpowiedzi

Najlepsza Odpowiedź!
2010-02-11T19:55:08+01:00
A)
2x+3y=14 - > 2x = 14 -3y / :2
3x-2y=8

x = 7-³/₂y
3 (7-³/₂y) - 2y = 8

x= 7-³/₂y
21- ⁹/₂ y -2y = 8

x = 7-³/₂y
-6½ y = 8-21

x= 7-³/₂y
-¹³/₂ y = -13 / *(-²/₁₃)

x=7-³/₂y
y = 2

x=7-³/₂ *2
y=2

x=7-3
y=2

x=4
y=2

b)
½x-2y=8 -> ½x = 8 +2y / *2
2x+5y=6

x = 16+4y
2* (16+4y) +5 y = 6

x = 16+4y
32+8y+5y = 6

x =16+4y
13y = 6-32

x=16+4y
13y = -26 / : 13

x = 16+4y
y = -2

x = 16 +4 * (-2)
y=-2

x = 16-8
y = -2

x = 8
y = -2

c)
½x-¾y=0 -> ½x = ¾y / *2
⅔x+1¼y=9

x = ³/₂ y
⅔ *³/₂ y +1¼y=9

x = ³/₂ y
y +1¼y=9

x = ³/₂ y
2¼y=9

x = ³/₂ y
⁹/₄y=9 / * ⁴/₉

x = ³/₂ y
y=4

x = ³/₂ *4
y=4

x = 6
y= 4

d)
3x+4y=1⅔ -> 3x = ⁵/₃ - 4y / :3
6x+3y=1¼

x = ⁵/₉ - ⁴/₃y
6 (⁵/₉ - ⁴/₃y) +3y=1¼

x = ⁵/₉ - ⁴/₃y
¹⁰/₃ - 8y +3y = ⁵/₄

x = ⁵/₉ - ⁴/₃y
- 8y +3y = ⁵/₄ - ¹⁰/₃

x = ⁵/₉ - ⁴/₃y
- 5y = -²⁵/₁₂ / : (-5)

x = ⁵/₉ - ⁴/₃y
y = -⁵/₁₂

x = ⁵/₉ - ⁴/₃ * (-⁵/₁₂)
y = -⁵/₁₂

X =⁵/₉ + ⁵/₉
y = -⁵/₁₂

X = ¹⁰/₉
y = -⁵/₁₂

X = 1 ¹/₉
y = -⁵/₁₂